2022
DOI: 10.1038/s41467-022-28076-3
|View full text |Cite
|
Sign up to set email alerts
|

Primary tumor associated macrophages activate programs of invasion and dormancy in disseminating tumor cells

Abstract: Metastases are initiated by disseminated tumor cells (DTCs) that colonize distant organs. Growing evidence suggests that the microenvironment of the primary tumor primes DTCs for dormant or proliferative fates. However, the manner in which this occurs remains poorly understood. Here, using the Window for High-Resolution Intravital Imaging of the Lung (WHRIL), we study the live lung longitudinally and follow the fate of individual DTCs that spontaneously disseminate from orthotopic breast tumors. We find that s… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
67
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 76 publications
(73 citation statements)
references
References 95 publications
0
67
0
Order By: Relevance
“…However, this view of dual-polarization is now regarded as an oversimplification. Polarization is a dynamic process, and many studies have instead focused on observing the functional diversity of TAMs [ 8 , 40 , 41 ] . In this study, we observed that microglia aggregated around the brain metastases in mouse models and NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…However, this view of dual-polarization is now regarded as an oversimplification. Polarization is a dynamic process, and many studies have instead focused on observing the functional diversity of TAMs [ 8 , 40 , 41 ] . In this study, we observed that microglia aggregated around the brain metastases in mouse models and NSCLC patients.…”
Section: Discussionmentioning
confidence: 99%
“…Similar default programs could occur in other organs in which ECs comprise a major Wnt source and were reported previously in different contexts 9,11 . Moreover, primary tumour-instructed remodelling of the niche could change the default state [45][46][47][48][49] . Additionally, the data strongly suggest that metastatic TCs actively inflicted a niche-EC gene program that resembled primary tumour EC signatures 29,50 and that could fuel TC proliferation by altering the biophysical properties of the micro-niche.…”
Section: Discussionmentioning
confidence: 99%
“…By tracking CTC transfer rates, the authors extrapolated half-life times in the circulation ranging from 40 to 260 s and intravasation rates between 60 and 107,000 CTCs/hour in several mouse models [ 84 ]. Another recent work showed that, compared to intravascularly injected tumor cells, disseminating tumor cells developed spontaneously are retained longer and at higher frequency, extravasate from the lung vasculature more quickly and have a greater chance of survival after extravasation [ 85 ], corroborating the involvement of other microenvironmental factors in dissemination, such as primary tumor-associated macrophages [ 85 , 86 ]. The importance of cancer cell–cell cooperation and tumor-associated microenvironment cells in CTC survival has been largely documented [ 87 ], firmly demonstrating that the formation of homotypic and heterotypic clusters in experimental models endows cancer cells with higher colonization ability and proliferation rate than single CTCs.…”
Section: Circulating Tumor Cells: the Kinetic Phase Of Metastasismentioning
confidence: 91%